How to Compute the Contact Angle inside an Opaque Capillary Tube: A Universal Equation (Adv. Theory Simul. 5/2022). Issue 5 (12th May 2022) - Zhao, Kaiqi; Sun, Lidong
Abstract : How to Compute the Contact Angle inside an Opaque Capillary Tube In article number 2100474, Kaiqi Zhao and Lidong Sun establish a universal equation to correlate the contact angle with an intrinsic property of a matter, i.e., the mass instead of the conventional height in a capillary tube. It is capable of evaluating the surface wettability inside capillary tubes in a more general way, regardless of the wettability, transparency, or materials.